2022
DOI: 10.3389/fgene.2022.868159
|View full text |Cite
|
Sign up to set email alerts
|

The EIF2AK4/rs4594236 AG/GG Genotype Is a Hazard Factor of Immunoglobulin Therapy Resistance in Southern Chinese Kawasaki Disease Patients

Abstract: Background: Kawasaki disease (KD) is an acute, self-limited vasculitis disorder of unknown etiology in children. Immunologic abnormalities were detected during the acute phase of KD, which reflected that the effect cells of the activated immune system markedly increased cytokine production. High-dose intravenous immunoglobulin (IVIG) therapy is effective in resolving inflammation from KD and reducing occurrence of coronary artery abnormalities. However, 10%–20% of KD patients have no response to IVIG therapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Therefore, more studies may be needed to elucidate the specific mechanisms by which GORASP2 affects the prognosis of CRC. Mutations in eukaryotic translation initiation Factor 2-αkinase 4 (EIF2AK4), a member of the kinase family that phosphorylates the alpha subunit of eukaryotic translation initiation Factor 2 (eIF2a), are common in pulmonary vein occlusive diseases and pulmonary capillary hemangiomatosis [35,36]. Alasiri et al [37] found that EIF2AK4 can cooperate with PERK and regulate the FOXO3 response to chemotherapy through JNK and AKT, thereby improving the prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more studies may be needed to elucidate the specific mechanisms by which GORASP2 affects the prognosis of CRC. Mutations in eukaryotic translation initiation Factor 2-αkinase 4 (EIF2AK4), a member of the kinase family that phosphorylates the alpha subunit of eukaryotic translation initiation Factor 2 (eIF2a), are common in pulmonary vein occlusive diseases and pulmonary capillary hemangiomatosis [35,36]. Alasiri et al [37] found that EIF2AK4 can cooperate with PERK and regulate the FOXO3 response to chemotherapy through JNK and AKT, thereby improving the prognosis of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the early years, our team has been focused on the progress of KD disease and the therapeutic effect, and achieved some exciting results. We found that single nucleotide polymorphisms (SNPs) of several genes (P2RY12, MRP4 and EIF2AK4 [35][36][37] ) were closely associated with IVIG treatment efficacy in KD; interestingly, these genes played important roles in immune response and cardiovascular-related functions. This study was the first one to focus on the effect of ZNF family (ZNF180 and ZNF112) on IVIG treatment resistance of KD.…”
Section: Discussionmentioning
confidence: 99%